2021
DOI: 10.1093/ofid/ofab537
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Obesity and Cardiometabolic Status by Integrase Inhibitor Use in REPRIEVE: A Propensity-Weighted Analysis of a Multinational Primary Cardiovascular Prevention Cohort of People With Human Immunodeficiency Virus

Abstract: Background Emerging data demonstrate that the use of integrase inhibitor (INSTI)-based antiretroviral treatment (ART) is associated with increased weight, but the cardiometabolic health consequences of increased weight remains poorly understood. Methods This analysis examined INSTI use (>6 months) at entry among REPRIEVE participants enrolled in High Income and Latin America/Caribbean Global Burden of Disease regions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 25 publications
1
20
1
Order By: Relevance
“…Prior literature has also demonstrated potential differential effects of INSTIs on weight gain among men and women. 21 , 22 In the NAMSAL study, women were more likely to experience a ≥10% change in weight over 48-week follow-up period compared to men. 23 In a multinational cohort of adults with well-controlled HIV, women on dolutegravir had a higher mean BMI and waist circumference than did women on an alternative ART regimen or men on dolutegravir.…”
Section: Discussionmentioning
confidence: 99%
“…Prior literature has also demonstrated potential differential effects of INSTIs on weight gain among men and women. 21 , 22 In the NAMSAL study, women were more likely to experience a ≥10% change in weight over 48-week follow-up period compared to men. 23 In a multinational cohort of adults with well-controlled HIV, women on dolutegravir had a higher mean BMI and waist circumference than did women on an alternative ART regimen or men on dolutegravir.…”
Section: Discussionmentioning
confidence: 99%
“…26 Previous studies have shown INSTI-based regimens to be associated with increased waist circumference, but not to a statistically significant extent. 2729 The statistically significant increase in waist circumference found in our study may have been due to our participants being older with more coexistent medical conditions including diabetes, CKD, and dyslipidemia. 29 However, the magnitude of the change was too small to be concerning.…”
Section: Resultsmentioning
confidence: 70%
“…Some studies have shown an association between ARV-related weight gain and/or body mass index changes and certain populations such as women and Black and Hispanic populations. However, further study is warranted to understand both of what predictors, if any, exist for this phenomenon, as well as the cardiovascular and metabolic implications associated with weight gain [13,[125][126][127][128][129][130].…”
Section: Safety/adverse Effectsmentioning
confidence: 99%